Loaves, beds, plants and Osiris : considerations about the emergence of the cult of Osiris - Roeten, Leo, (Archaeopress Egyptology ;)
The emergence of the cult of Osiris is, in most cases, dated to the end of the 5th dynasty, the period in which the name of Osiris appears in writing, and it is commonly held that before this period not a trace of the cult can be discerned. This study is intended to investigate whether this emergence was really so sudden, or if there is evidence to suggest this appearance was preceded by a period of development of the theology and mythology of the cult. One of the most important aspects of the mythology of the cult is the rebirth of Osiris. In the theology of the cult this rebirth was projected on mortal men, and led to the postulation that every human being, whether royal or non-royal, had the possibility to attain eternal life after death. What made this cult even more attractive is that this eternal life was not confined to the tomb, as it used to be for non-royalty. The study is concerned with the rebirth possibilities of non-royal persons and aims to determine the chronological development of the rebirth connotations of the various decoration themes that were used in the chapel of Old Kingdom tombs. The decoration themes that are the subject of the determinations are the group of bed-scenes consisting of the bed-making scene and the marital bed-scene, the development in form and length of the bread loaves on the offering table, the different aspects of the scenes in which the "lotus" flower is depicted, and the marsh scenes.